(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study focuses on identifying circumstances where Indian retail SMEs adopt digital payment systems through the convergence of technology perception constructs and their respective performance outcomes. This paper attempts to bridge severe limitations of previous studies to include retail SME-specific questions such as digital divide theory definitions, sociodemographic parameters, psychological adaptation constructs, and trust-specific areas for consideration. The paper does supply there is empirical evidence on the outcome of digital payment system implementation for enhancing revenue and improving operating efficiencies. The paper aims to collect data using a structured questionnaire technique. This paper uses a quantitative method to target 384 retail managers or digital payment implementers. Some of the key parameters found to favourably affect digital payment acceptance parameters include perceived values, usability parameters, and security or trust parameters. By employing validity using Confirmatory Factor Analysis and Structural Equation Model Analysis for this purpose, it aids in adapting parameters to enhance operating efficiency and business performance. In essence, it concludes for digital payment systems to find acceptance among retail SMEs to support both transactional and strategic efficiency parameters. Lastly, this paper on digital payments concludes with suggestions and proposals to respective authorities and Fintech corporations to ease retail usage of digital payment systems among Indian businesses.